ECONOMIC VALUE OF RESERVOIR PLTA KOTO PANJANG KAMPAR RIAU PROVINSI USING PRODUCTIVITY APPROACH RESIDUAL RENT - Sihombing, Fitriani; Zulkarnaini, Zulkarnaini; Warningsih, Trisla (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The research was conducted in February 2018 which is located in Koto Panjang hydroelectric reservoir of Kampar Regency of Riau province. This study aims to analyze the total cost of production on the business of fish Mas, Analyzing the revenue / gross income in the business of Mas fish, Analyzing the level of profit / net income in the business of Mas fish, Analyzing the economic value of the Mas fish farming, the method used in This research is a Simple Random Sampling method (randomly) with the number of respondents as much as 29 people cultivators. Data analysis used is production cost analysis, gross income analysis, net income analysis, Residual rent analysis. The results showed the annual production cost of IDR. 25.101.280.000, gross revenue IDR. 41.037.150.000, net income IDR. 15.935.870.000. The number of goldfish production per year is 1.609,3 tons. The economic value of KJA's fishery activities in Koto Panjang hydropower reservoir is IDR. 20.472.752.000 from the total KJA units of 1,546 units. Keywords: Economic Value, Production, Revenue, floating net cages